2021
DOI: 10.1016/j.scs.2020.102586
|View full text |Cite
|
Sign up to set email alerts
|

Modeling urban sprinkling with cellular automata

Abstract: This paper presents a spatiotemporal analysis to simulate and project urban sprinkling with coupled cellular automata (CA) and multinomial logistic regression (MLR) model. Our case study, the Basilicata region, south of Italy, is characterized by urban sprinkling-literally "a small amount of urban territory distributed in scattered particles". The region is witnessing a decoupled growth between demographic trend and urban expansion. We applied a coupled approach based on CA and MLR for urban sprinkling modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Looking at Figure 2, which shows the increase in artificial surfaces in 2018 compared to those already existing in 2000, it is possible to recognize different dynamics. Considering that urban growth processes in Italy occurred as described by Romano et al [46,48,49], we highlight that they are still ongoing, and we also point out the lack of both an adequate monitoring system and an effective interpretative framework of the effects that these transformations exert on environmental and territorial components.…”
Section: Area Of Studymentioning
confidence: 71%
See 2 more Smart Citations
“…Looking at Figure 2, which shows the increase in artificial surfaces in 2018 compared to those already existing in 2000, it is possible to recognize different dynamics. Considering that urban growth processes in Italy occurred as described by Romano et al [46,48,49], we highlight that they are still ongoing, and we also point out the lack of both an adequate monitoring system and an effective interpretative framework of the effects that these transformations exert on environmental and territorial components.…”
Section: Area Of Studymentioning
confidence: 71%
“…Considering that urban growth processes in Italy occurred as described by Romano et al [46,48,49], we highlight that they are still ongoing, and we also point out the lack of both an adequate monitoring system and an effective interpretative framework of the effects that these transformations exert on environmental and territorial components.…”
Section: Area Of Studymentioning
confidence: 71%
See 1 more Smart Citation
“…The future visions are coded into spatially and temporally explicit land use transition rules to be simulated through a land use/cover change (LUCC) model (as shown in Table 1). Land use change models are widely used to simulate future land use patterns that assume no major changes in socioeconomic settings or policies so that the future changes are just an extrapolation of observed historical changes (even though many land use change models that have examined past changes and/or simulated possible future land use patterns have found that many demographic variables are important drivers of land use changes (Puertas et al, 2014;Rienow and Goetzke 2015;Ku, 2016;Vermeiren et al, 2016;Saganeiti et al, 2021).…”
Section: Participatory Visioning and Local Landuse Approaches To Mode...mentioning
confidence: 99%
“…This phenomenon is contrary to the findings of many observational studies that suggest that a region can drive the development of surrounding areas once it has reached a developed state. If neighborhood interaction is to be considered, the simulation framework must be able to discretize the whole into individuals, and the model to do this is cellular automata (CA) [48,59], at present the most widely used bottom-up model for simulating urban pattern evolution [49].…”
Section: Introductionmentioning
confidence: 99%